1973
DOI: 10.1007/bf01395979
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gamma ray transitions and lifetimes in35Cl

Abstract: Fortyeight resonances of the 34S(p, y)aSCl reaction in the proton range Ep= 1 --2 MeV have been observed. Gamma decay of twentyeight of these was investigated by means of a 55 em 3 Ge(Li) detector, and the energies and branching ratios of several bound states have been determined. The Q-value was found to be 6367.0_ 1.5keV. The lifetimes 150__20, 400__+140, 19-t-4, 14-t-2, 145+50, 20+5, 20+4, 42+4 and 7-1-3 fs were determined with the DSA method for the states at 1219, 1763, 2694, 3003, 3944, 3967, 4059, 4178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For a variation in rate of a factor of ±100, a reasonable assumption as the rate used is the result of a theoretical statistical model with no experimental input, the final abundances of several key nuclei, including 34 S, 35 Cl, and 37 Ar, were found to vary by as much as 10-100X. Some presolar grains are known to condense in the ashes of novae [2,3], making observed isotopic ratios into "thermometers" of the explosion; for masses above A∼ 20, these ratios are influenced by po-§ current address: FLIR Systems Inc., Oak Ridge, Previous studies of the 34 S(p,γ) reaction [4][5][6][7][8][9][10] have mostly focused on energies 1-3 MeV above the proton threshold at 6370.6 keV [11], higher in energy than is relevant to most astrophysical scenarios including novae. One direct measurement [10] was able to determine the strength of a resonance of unknown spin/parity in 34 S+p around E r = 500 keV, but direct measurements at lower energies will become increasingly difficult, with cross sections dropping by orders of magnitude as the Gamow window is approached.…”
Section: Astrophysical Motivationmentioning
confidence: 99%
“…For a variation in rate of a factor of ±100, a reasonable assumption as the rate used is the result of a theoretical statistical model with no experimental input, the final abundances of several key nuclei, including 34 S, 35 Cl, and 37 Ar, were found to vary by as much as 10-100X. Some presolar grains are known to condense in the ashes of novae [2,3], making observed isotopic ratios into "thermometers" of the explosion; for masses above A∼ 20, these ratios are influenced by po-§ current address: FLIR Systems Inc., Oak Ridge, Previous studies of the 34 S(p,γ) reaction [4][5][6][7][8][9][10] have mostly focused on energies 1-3 MeV above the proton threshold at 6370.6 keV [11], higher in energy than is relevant to most astrophysical scenarios including novae. One direct measurement [10] was able to determine the strength of a resonance of unknown spin/parity in 34 S+p around E r = 500 keV, but direct measurements at lower energies will become increasingly difficult, with cross sections dropping by orders of magnitude as the Gamow window is approached.…”
Section: Astrophysical Motivationmentioning
confidence: 99%
“…A detailed analysis of the excited state of 35 Cl and a discussion of the separation and the spin assignment of the two 5.65-MeV states can be found in [56]. The excitation energy resulting from the mean values of the data gives the respective energies of 5646 (2) keV and 5654 (2) keV.…”
Section: B Excited States Of the Imme A = 35 Quartetmentioning
confidence: 99%
“…For the excited state of 35 Cl, as summarized in [31], the experimental data are not precise enough and show as well some discrepancies (see [53] and references therein). The energy level scheme of 35 Cl exhibits a 'double' peak around 5.65 MeV, which has been thoroughly investigated [53,54,55,56,57]. Previous work on the IMME showed that the energy of the excited state for 33 Cl was wrongly calculated from the center-of-mass to the laboratory frame [8].…”
Section: B Excited States Of the Imme A = 35 Quartetmentioning
confidence: 99%